Investors’ Delight? Climate Risk in Stock Valuation during COVID-19 and Beyond - Andrea Jacob (MDPI AG, 2021)
We use the COVID-19 pandemic period in 2020 as an exogenous shock event to assess in how far climate risks measured by carbon exposure have entered and established themselves in the valuation of global stocks. In addition to descriptive analyses, we conduct cross-sectional panel regressions to assess the influence of carbon intensity levels on return and risk characteristics during and after the shock period. Furthermore, a difference-in-differences model setup allows us to infer whether these influences were significantly different when comparing pre-shock, shock, and post-shock periods. We find that carbon intensity affected returns significantly and negatively during a time of high uncertainty. In fact, high-emitting stocks suffered significantly more compared to the pre-crisis period. However, they could make up for their additional losses in the recovery period. In line with their high-risk exposure towards stranded assets and climate policy uncertainty, carbon-intensive stocks face higher risk levels in more stable economic times, thus justifying a carbon premium.